Education, Work Ability, and Job Stress as Determinants of Employee Productivity in Jakarta’s MSMEs - Salsa Mukminah; Didin Hikmah Perkasa (Journal of Social Commerce, 2026)
This study investigates the determinants of employee productivity in Jakarta's Micro, Small, and Medium Enterprises (MSMEs), focusing on the roles of education, work ability, and job stress. As MSMEs contribute approximately 61% to Indonesia's GDP and employ over 97% of the workforce, understanding productivity drivers in this sector is crucial for economic development. Using a quantitative approach, data were collected from 136 MSME owners and employees across various sectors in Jakarta through structured questionnaires. Partial Least Squares Structural Equation Modeling (PLS-SEM) was employed to analyze the relationships among variables. The findings reveal that work ability exerts the strongest positive influence on productivity (β = 0.473), followed by education (β = 0.257), while job stress negatively affects productivity (β = -0.176). The model explains 30.9% of productivity variance, indicating that practical competencies outweigh formal credentials in determining work performance. These results challenge conventional recruitment practices that prioritize educational qualifications over practical skills. The study provides actionable insights for MSME management to enhance productivity through competency-based hiring, continuous skill development programs, and systematic stress management interventions, ultimately contributing to sustainable business growth in Indonesia's dynamic entrepreneurial ecosystem.